Thermal investigation of LED array with multiple packages based on the superposition method. Issue 7 (July 2015) - Shi, Dong; Feng, Shiwei; Zhang, Yamin; Qiao, Yanbin; Deng, Bing
Abstract In this paper, the superposition method is used to investigate the complete temperature field of a light-emitting diode (LED) packaging substrate, based on the results of transient temperature rise measurements and the thermal resistance coupling matrix. The feasibility of use of the superposition method in an LED array with multiple packages has been proved first by temperature comparisons with the simultaneous operation of an array (5×5) of 25 high power LEDs mounted on a metal core printed circuit board (MCPCB). Compared with existing approaches, the superposition method will measure the internal temperature of chip directly, accurately and nondestructively. According to the relatively accurate and reliable self-heating and coupling temperature rise data, optimization scheme of LED lamp with multiple packages is proposed. The results show that increasing the heat source separation distance and improving the thermal conductivity of thermal interface materials will reduce the temperature rise and thermal non-uniformity.